INTERNET JURNALISTIKADA GIPERTEKSTTIŃ ULÍWMA TEORIYALÍQ KONCEPCIYASÍ - Begniyazova, Q. (SCIENCE and SOCIETY, 2024)
In the article, the creative genesis, nature, scientific theory of hypertext, which is considered one of the three characteristics of internet journalism that can be distinguished from other media, is proven by the theses presented in foreign and national studies. Hypertext is both a technical and creative phenomenon at the same time, which interweaves texts within the distance of space and time. It features article expansion.